Primary Actinomycosis of the Leg: A Case Report and Literature Review - Alabdalaaly, Dr. Norah Ibrahim; Albahli, Dr. Mashael Suliman; Almutairi, Dr. Ayed Ibrahim (International Journal of Innovative Research in Medical Science, 2022)
Actinomycosis is an indolent, slowly progressive, suppurative infection caused by gram-positive branching bacteria of the genus Actinomyces. The disease actinomycosis most commonly occurs in 3 body regions: cervicofacial (55% of patients), abdominopelvic (20%), and pulmonothoracic (15%). Primary infection of an extremity is an uncommon feature of actinomycosis. We present a case of rare primary Actinomycosis of the lower extremity.